Improving conceptual understanding of physics by experiential learning with the aid of apps - Ishak, Izdihar; Mat Nawi, Mohd Nazir; Husin, Hafiz; Kamaluddin, Ammar Haikal (Asian Scholars Network, 2025)
Physics is always a challenging subject for students. One method used in improving the conceptual understanding of Physics by experiential learning with the aid of apps as a part of mobile learning. This paper will discuss the experience in CFS regarding the method use and the effect to the understanding of Physics. The researcher had developed two apps, one for calculating angular momentum and the other for calculating the frequency of sound in musical instruments. The effect of using experiential learning with the aid of apps is describe and elaborated. The researcher also carried out a survey on the student's experience using Likert scale of 1-5. From the response, 18% gave a score of 4 and 81% gave a score of 5. This indicates that most of them found that experience learning with the aid of apps really aids in their understanding of Physics concepts.